1994
DOI: 10.1111/j.1600-051x.1994.tb00720.x
|View full text |Cite
|
Sign up to set email alerts
|

Type I collagen carboxyterminal telopeptide in human gingival crevicular fluid in different clinical conditions and after periodontal treatment

Abstract: A total of 126 gingival crevicular fluid (GCF) samples were collected from 20 adults using paper strips. Patients were divided into a periodontitis-affected group (13 subjects) and a periodontitis-free group (7 subjects) by pocket depth and radiological bone loss. 4 subjects from the periodontitis-affected group received a single episode of periodontal treatment (scaling, root planing and curettage) and GCF samples were collected 2, 5, 10, 20 and 40 days after treatment. Type I collagen carboxyterminal telopep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
51
1
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 23 publications
2
51
1
1
Order By: Relevance
“…Therefore, ICTP may be a first generation pyridinoline cross-link detectable in GCF. Newer methods may involve the use of deoxypyridinoline and other cross-links as immunodetection methods are optimized.The results of this investigation extend previous studies (Giannobile et al 1995, Talonpoika & Hämäläinen 1994) that demonstrated a relationship between ICTP and inflammatory periodontal disease. Shibutani et al (1997) showed similar findings with deoxypyridinoline (found most abundantly in bone and dentin) measured in the GCF, serum and urine during experimental periodontitis in dogs.…”
supporting
confidence: 89%
See 3 more Smart Citations
“…Therefore, ICTP may be a first generation pyridinoline cross-link detectable in GCF. Newer methods may involve the use of deoxypyridinoline and other cross-links as immunodetection methods are optimized.The results of this investigation extend previous studies (Giannobile et al 1995, Talonpoika & Hämäläinen 1994) that demonstrated a relationship between ICTP and inflammatory periodontal disease. Shibutani et al (1997) showed similar findings with deoxypyridinoline (found most abundantly in bone and dentin) measured in the GCF, serum and urine during experimental periodontitis in dogs.…”
supporting
confidence: 89%
“…These investigations have shown that ICTP correlated strongly with radiographic bone level and pocket depth and was significantly higher at periodontitis sites compared to non-periodontitis sites (Talonpoika & Hämäläinen 1994). In a ligature-induced experimental periodontitis study in dogs, the GCF levels of pyridinoline cross-links (ICTP and deoxypyridinoline) significantly increased during the development of attachment loss and osteoclastic bone resorption (Giannobile et al 1995, Shibutani et al 1997.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…The increased recognition of the interactions between the cells of the immune and skeletal system has led to the seeking of a variety of regulatory molecules that play a role in the progression of periodontal disease [25][26][27]. In previous studies, the bestknown markers of the bone turnover have been widely investigated in GCF samples of patients with different periodontal diseases and implicated to be associated with the progression of periodontal diseases [28][29][30]. Several investigations provided contradictory evidence about the role of osteocalcin in GCF of patients with periodontitis [31][32][33].…”
Section: Introductionmentioning
confidence: 99%